Kinetika Pembentukan Struvite Kristal Menggunakan Zeolit Alam sebagai Adsorben pada Aeration Cone Column Crystallizer - Eko Ariyanto; Yuyun Niyati; Dian Kharismadewi; Robiah Robiah (Jurnal Rekayasa Proses, 2020)
Wastewater from the fertilizer industry contains a high concentration of PO43- and NH4+. Those ions formed deposits that frequently clogged the conduits and reduced the pump efficiency of the wastewater treatment plant. A high concentration of PO43- and NH4+ in this wastewater can be used as a secondary source of PO43- fertilizer through the recovery process into struvite compounds (MgNH4PO4.6H2O). In this research, Struvite was crystallized in Aeration Cone Column Crystallizer (ACCC) with Magnesium modified natural Zeolite (Zeo-Mg) as adsorbent. Research also has been done using the Batch process, and the results were used as basis variables in the ACCC system. Effects of Zeolite activation, amounts of Zeo-Mg (10 – 30 g), PO43- and NH4+reactant ratio (1:1 – 1:3), pH (6 – 9), and reaction time (0 – 60 minutes) to the removal percentage of PO43- were used as research parameters that analyzed in struvite crystallization process. Zeo-Mg and struvite produced were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy. Research results in the ACCC system with Zeo-Mg as adsorbent showed that the percentage of PO43- removal was 65% in 16 minutes and followed pseudo-first-order reaction kinetics with a reaction rate constant of 0.21 min-1. The PO43- removal reached equilibrium at pH 8.10 after 28 minutes. Simultaneous removal of PO43- to formed struvite crystals using Zeo-Mg as an adsorbent and without the addition of Mg ions solution in the ACCC system is a novel process in wastewater treatment. Moreover, this PO43- recovery process can be implemented in the industrial scale due to the practical operation.A B S T R A KAir limbah industri pupuk banyak mengandung PO43- dan NH4+. Ion-ion ini membentuk endapan yang seringkali menyumbat aliran pipa yang menyebabkan penurunan efisiensi pompa di instalasi pengolahan air limbah. Kandungan PO43- dan NH4+ berkonsentrasi tinggi ini dapat dijadikan sumber sekunder untuk membuat pupuk PO43- dengan melakukan recovery sebagai senyawa struvite (MgNH4PO4.6H2O). Pada penelitian ini, struvite dibentuk menjadi kristal menggunakan Aeration Cone Column Crystallizer (ACCC) dengan adsorben zeolit alam yang telah dimodifikasi menggunakan ion magnesium (Zeo-Mg). Penelitian juga dilakukan dengan menggunakan proses batch, yang hasilnya dijadikan basis variabel pada sistem ACCC. Pengaruh pengaktifan zeolit, penambahan Zeo-Mg (10–30 g), rasio reaktan PO43- dan NH4+ (1:1–1:3), perubahan pH larutan (6–9), dan lamanya waktu reaksi (0–60) menit terhadap persentase penyisihan PO43- menjadi parameter yang dianalisis pada proses kristalisasi struvite. Zeo-Mg dan struvite yang dihasilkan dianalisis menggunakan scanning electron microscopy dan energy dispersive X-ray spectroscopy. Penelitian menggunakan ACCC menghasilkan persentase penyisihan PO43- dengan adsorben Zeo-Mg sebesar 65% dalam 16 menit dan mengikuti persamaan kinetika reaksi orde satu, dengan konstanta laju reaksi 0,21 min-1. Penyisihan PO43- mencapai kesetimbangan pada pH 8,10 setelah 28 menit. Proses pemisahan PO43- dengan adsorben Zeo-Mg menjadi struvite secara berkesinambungan pada sistem ACCC merupakan proses baru pengolahan air limbah. Selain itu, proses pemanfaatan kembali PO43- ini dapat diterapkan ke dalam skala industri karena kemudahan dalam pengoperasiannya.